New Technologies, Mobility and Security - Labiod, Houda; Badra, Mohamad; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
NTMS'2007 is the first IFIP International Conference on New Technologies, Mobility and Security that was held from May 2 to May 4, 2007 in Paris, France. NTMS'2007 aims at fostering advances in the areas of New Technologies, Wireless Networks, Mobile Computing, Ad hoc and Ambient Networks, QoS, Network Security and E-commerce, to mention a few, and provides a dynamic forum for researchers, students and professionals to present their state-of-the-art research and development in these interesting areas. The event was combined with tutorial sessions and workshops. Tutorials preceded the main program, aiming at the dissemination of mature knowledge and technology advances in the field. One Workshop immediately followed the main conference, offering the opportunity for a more focused exchange of ideas and presentation of on-going research relevant to selected topics.
Critical Transmission Range for Connectivity in Ad-Hoc Networks -- ScatterFactory: An Architecture Centric Framework for Wireless Sensor Networks -- Performance of Multi-Hop Relaying Systems over Weibull Fading Channels -- Performance Study of a New MAC Algorithm to Reduce Energy and Delay in Wireless Sensor Networks -- A Fast and Efficient Source Authentication Solution for Broadcasting in Wireless Sensor Networks -- TMN Management Systems using a Grid based agnostic middleware -- Direct RF Conversion Transceivers as a Base for Designing Dynamic Spectrum Allocation Systems -- Scalable Communication for High Performance and Inexpensive Reliable Strict QoS -- A User Interface for Resource Management in a Mobile Environment -- Application of Reuse Partitioning Concept to the IEEE 802.16 System: Design and Analysis -- Evaluation of the performance of the SLoPS: Available Bandwidth Estimation Technique in IEEE 802.11b Wireless Networks -- Quality of Service Provisioning Issue of Accessing IP Multimedia Subsystem via Wireless LANS -- Three-color Marking with MLCN for Cross-layer TCP Congestion Control in Multihop Mobile Ad-hoc Networks -- Joint Cross-layer Power Control and FEC Design for TCP Westwood+ in Hybrid Wireless-Wired Networks -- Joint Cross-layer and Dynamic Subcarrier Allocation Design for Multicast OFDM Networks -- Handover Optimization for vehicle NEMO Networks -- Introducing L3 network-based mobility management for mobility-unaware IP hosts -- WiMax-based Vertical handovers for Next Generation Networks -- A System-Level Analysis of Power Consumption & Optimizations in 3G Mobile Devices -- Runtime software modification method used on COTS system for high-availability network service -- MRC Diversity Reception of OFDM with M-ary Modulation over Frequency-Selective Nakagami-m Fading Channels -- Performance and Flexibility of Open Source Routing Software1 -- Emerging Wireless Communication Technologies1 -- Upgrade of a Composite-Star Optical Network -- An Adaptive Approach to Optimize Software Component Quality Predictive Models:Case of Stability -- Transport Information Collection Protocol with clustering of information sources -- Virtual Authentication Ring for Securing Network Operations -- Federated Dynamic Authentication and Authorization in Daidalos -- Secure and Fast Roaming in 802.11 WLANS -- Wormhole Detection Method based on Location in Wireless Ad-Hoc Networks -- An Effective Defense Against Spoofed IP Traffic -- On the security of quantum networks: a proposal framework and its capacity -- An adaptive security Framework for ad hoc networks -- Localization with witnesses -- SAACCESS: Secured Ad hoc ACCess framework -- Hiding User Credentials during the TLS authentication phase -- Enhanced Smart-Card-Based Authentication Scheme Providing Forward-Secure Key Agreement -- A Mathematical Framework for Risk Assessment -- An Efficient Hybrid Chaotic Image Encryption Scheme -- A Model based on Parallel Intrusion Detection Systems for High Speed Networking Security -- A Dynamic Policy based Security Architecture for Mobile Agents -- A Scheme for Intrusion Detection and Response in Ad Hoc Networks -- Query Answering in Distributed Description Logics -- WSRank: A New Algorithm for Ranking Web Services -- Authenticated Web Services: A WS-Security Based Implementation* -- An Architectural Model for a Mobile Agents System Interoperability -- P2PNet: A Simulation Architecture for Large-scale P2P systems -- A Middleware for Managing Sensory Information in Pervasive Environments -- An Advanced Metering Infrastructure for Future Energy Networks -- Internet Topology Based Identifier Assignment for Tree-based DHTs -- A Secure Dynamic Remote User Authentication without any Secure Channel -- Cross-Layer Optimization for Dynamic Rate Allocation in a Multi-User Video Streaming System -- Design and implementation of a Decentralized Access Control System (DACS) and an application -- Monitoring and Security of Container Transports -- A new approach for anomalies resolution within filtering rules -- SPMCS: A Scalable Architecture for Peer to Peer Multiparty Conferencing -- A New Authenticated Key Agreement Protocol -- Growing Hierarchical Self-Organizing Map for Alarm Filtering in Network Intrusion Detection Systems -- AGDH (Asymmetric Group Diffie Hellman) An Efficient and Dynamic Group Key Ageement Protocol for Ad Hoc Networks.
Keywords: ENGINEERING; TELECOMMUNICATION; ENGINEERING; COMMUNICATIONS ENGINEERING, NETWORKS; SIGNAL, IMAGE AND SPEECH PROCESSING